Newspaper Editors' Interactions with Journalistic Serendipity. Issue 4 (2nd October 2021) - Bird-Meyer, Matthew; Erdelez, Sanda
ABSTRACT: This qualitative study explores the information behavior of newspaper reporters regarding their serendipitous encounters with information that lead to story ideas, and how newspaper editors affect reporters' ability to pursue such encountered ideas. As an interdisciplinary examination in human information behavior and journalism studies, behaviors and routines emerged that encouraged and potentially limited certain behaviors and routines. The findings also identify behaviors wherein newspaper editors match reporters with certain traits to certain story assignments.